Sensitivity and specificity of the three Whooley and Arroll questions for detecting perinatal depression in Mexican women - Laura Navarrete; Lourdes Nieto; Ma. Asunción Lara; Ma. del Carmen Lara (Instituto Nacional de Salud Pública, 2018)
Objective. To evaluate the sensitivity and specificity of the Two Whooley questions and the Arroll question, using the SCID, The Structured Clinical Interview (SCID-I) as the gold standard for detecting perinatal depression. Materials and methods. We interviewed 210 women during pregnancy and 6 months postpartum. Results. The criterion with the greatest sensitivity was responding positively to either Whooley question (pregnancy= 94.7 %; postpartum=100.0%), while the most specific criterion was responding positively to the two Whooley questions plus the Arroll question (Pregnancy=90.0% Postpartum = 85.7%). Conclusion. The Whooley and Arroll questions have adequate psychometric properties to detect possible cases of depression during the perinatal period. They can be applied during prenatal check-ups and postpartum consultations. Timely detection of women at risk of perinatal depression can contribute to their treatment for reducing their adverse consequences in mothers and infants.